- NATIONAL CONTACT POINTS AS NON-JUDICIAL MECHANISMS FOR ACCESS TO JUSTICE. AN ANALYSIS FROM THE CASES PROCESSED IN ARGENTINA AND SPAIN. (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
The objective of this work is to investigate the resolution mechanism for specific instances of the National Contact Points of the OECD Guidelines for Multinational Enterprises on Responsible Business Conduct as a non-judicial mechanism for access to justice. To this end, the cases processed in Argentina (period 2004-2021) and Spain (period 2001-2023) are analyzed, in order to establish limits and possibilities for their use by social actors, such as unions and NGOs in the context of economic globalization and transnational law.
Keywords: access to justice, national contact point, specific instances, multinational enterprises.